KG-oscillators in a spinning cosmic string spacetime and an external magnetic field - Mustafa, Omar; Guvendi, Abdullah (Nuclear physics. B, 2025)
We study the Klein-Gordon (KG) oscillators in a spinning cosmic string spacetime and an external magnetic field. The corresponding KG-equation is shown to admit a solution in the form of the confluent hypergeometric functions/polynomials. Consequently, the corresponding energies are shown to be given in a quadratic equation of delicate nature that has to be solved in an orderly manner (for it involves the energies for KG-particles/antiparticles, E=E±=±|E| along with the magnetic quantum number m=m±=±|m|). Following a case-by-case strategy allowed us to clearly observe the effects of the spinning cosmic string on the spectroscopic structure of the KG-oscillators. Interestingly, we have observed that the coexistence of a spinning cosmic string and an external magnetic field eliminates the effect of the wedge parameter for KG-particles (E=E+), with m=m+, but not for the KG-antiparticles (E=E−), with m=m−. Such coexistence is observed to break the symmetry of the energies of the KG-particles and the antiparticles about E=0 for the KG-oscillators. However, for KG-particles (E=E+), with m=m−, and KG-antiparticles (E=E−), with m=m+, they are found to be unfortunate because they are indeterminable. Moreover, for the spinning parameter β>>1, the clustering of the energy levels is observed eminent to indicate that there is no distinction between energy levels at such values of β.